FC 113UTILITY OF A SINGLE ITCH-RELATED QUESTION AND THE SKINDEX-10 QUESTIONNAIRE FOR ASSESSING PRURITUS AND PREDICTING HEALTH RELATED QUALITY OF LIFE IN HEMODIALYSIS PATIENTS. (29th May 2021) - Lopes, Marcelo; Karaboyas, Angelo; Tsuruya, Kazuhiko; Al Salmi, Issa; Sukul, Nidhi; Asgari, Elham; Alyousef, Anas; Thilo, Schaufler; Walpen, Sebastian; Menzaghi, Frederique; Pisoni, Ronald
Abstract: Background and Aims: Chronic kidney disease-associated pruritus (CKD-aP) has been linked with comorbid conditions, and poorer mental and physical health-related quality-of-life (HR-QOL) in hemodialysis (HD) patients. The Skindex-10 questionnaire and a single itch-related question from the KDQOL-36 have been used to evaluate the impact of pruritus in HD patients. In this analysis, we investigated the performance of the single question and the Skindex-10 as predictors of HR-QOL in HD patients. Method: We analyzed data from 4940 HD patients from 17 countries enrolled during year 2 of phase 5 of the Dialysis Outcomes and Practice Patterns Study (DOPPS, 2013): Belgium, Canada, Germany, the Gulf Cooperation Council (GCC) (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, United Arab Emirates), Italy, Japan, Russia, Spain, Sweden, Turkey, the UK, and the US. The Skindex-10 scores were calculated as per Mathur et al. (2010): responses to each of the 10 questions (0-6 scale), pertaining to how often patients were bothered by itchy skin in the past week, were summed to create a total summary score (range 0-60, with 0 indicating not at all bothered) and 3 subdomain scores [i.e., itching (disease) and its impact on mood/emotional and social functioning]. The itch-related single question from the KDQOL-36 asked: "During the past 4 weeks, to what extent were you bothered by itchy skin?" with response options including "not at all, somewhat, moderately, very much, extremely". Itch-related measures were collected concurrently with HR-QOL measures: Physical (PCS) and Mental (MCS) Component Summary scores, derived from the SF-12. We calculated the Spearman correlation coefficient between the Skindex-10 (total score and for each of its 3 domains) and the single question. We used separate linear regression models to evaluate the predictive power of 1) the Skindex-10 score, 2) the single itch question, and 3) both, on PCS and MCS outcomes, based on R-squared values. Results: Skindex-10 scores varied across countries; the proportion of patients with a very high Skindex-10 score (≥50) ranged from 12% in the GCC to only 2% in Italy, Russia and Sweden. Across all countries, 55% had a Skindex-10 score=0. For the single pruritus question, 37% answered that they were not at all bothered while 16% were very much or extremely bothered by itchy skin. The correlation between the single question and Skindex-10 was 0.71 overall, 0.72 for the disease domain, 0.62 for the social domain, and 0.70 for the emotional domain. Patient characteristics were similar across categories of both pruritus measures. Regression analyses showed that every 10 points higher in the Skindex-10 score was associated with 1.2 point lower PCS (95% CI: -1.4, -0.9) and 1.5 point lower MCS (95% CI: -1.7, -1.3) scores. Similarly, the single question showed increasingly poorer PCS and MCS scores with a greater degree of being bothered by pruritus: compared with patients not at all bothered by itchy skin, patients who were moderately bothered had 4.8 point lower PCS (-5.7, -3.9) and 4.3 point lower MCS (-5.3, -3.3) scores. The R-squared for PCS was 0.065 when using the single question and only 0.033 when using the Skindex-10 as the predictor. R-squared was also higher for MCS when using the single question (0.056) vs. Skindex-10 (0.052). When including both pruritus measures, the predictive power for PCS did not improve compared to the single question (R2=0.065), while increasing only slightly (R2=0.063) for MCS. Conclusion: The single KDQOL-36 question about the extent bothered by itchy skin over the past 4 weeks was highly correlated with the Skindex-10 score and at least as predictive – if not more – of key HR-QOL measures as the Skindex-10. In daily clinical practice, utilizing 1 simple question about the extent patients are bothered by itchy skin can be a feasible and efficient way for routine assessment of pruritus to better identify HD patients with not only CKD-aP but also poorer HR-QoL.